Diagnostic expectations and stock returns - Bordalo, P; Gennaioli, N; La Porta, R; Shleifer, A (Wiley, 2019)
We revisit LaPorta’s (1996) finding that returns on stocks with the most optimistic analyst long-term earnings growth forecasts are lower than those for stocks with the most pessimistic forecasts. We document the joint dynamics of fundamentals, expectations, and returns of these portfolios, and explain the facts using a model of belief formation based on the representativeness heuristic. Analysts forecast fundamentals from observed earnings growth, but overreact to news by exaggerating the probability of states that have become objectively more likely. We find supportive evidence for the model’s distinctive predictions. An estimation of the model quantitatively accounts for the key patterns.